British Association of Dermatologists' guidelines for the management of pemphigus vulgaris 2017. (30th November 2017) - Harman, K.E.; Brown, D.; Exton, L.S.; Groves, R.W.; Hampton, P.J.; Mohd Mustapa, M.F.; Setterfield, J.F.; Yesudian, P.D.
Abstract : Plain language summary available online